Political Policy Struggle Of The New Order Against Development Of State Aliyah Madrasah In Indonesia (1966-1998) - Ahmad Ali Riyadi; Khoiriyah Khoiriyah; A. Syafi' AS. (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2021)
This study aims to examine the New Order's political policies towards the development of State Aliyah Madrasah in Indonesia. The method of this study is a historical approach. Data obtained through literature review, both primary and secondary. Analysis of research data with content analysis. The results obtained are the development of Madrasah Aliyah influenced by the relationship of the New Order to Political Islam, that is, if the relationship between the New Order and Islam improves, there will be significant progress towards the development of the Aliyah madrasa. There are policies that benefit the development of Madrasah Aliyah, both in terms of recognition of formal legality and institutional quality.